“Evaluation of superoxide Dismutase (SOD) enzyme level and some indicators in people exposed to smoke” - Marwa Azeez Akoul; Dina Jamal Awad; Sarah Salam Talib1; Ruqayya Hadi Yunis; Shimaa Dalil Mohammed; Sondos Abdul Rahman Khalaf; Duha Hazime Hadi; Bahaa Aldeen Khaled Jwad; Aisha Omar Majeed (International Journal of Toxins and Toxics, 2024)
The aim of this study is to assess the level of SOD enzyme and its impact in people who are exposed to smoking, in addition to measuring C-interactive protein, and finally measure a complete picture of blood samples taken from patients. The results of the current study showed there is a significant differences (p<0.05) in the activity of the SOD. The mean of SOD activity in patient was 127.9 U/ml while the mean of the enzyme in the control was 96.00 U/ ml. CBC and CRP analysis for all (case and control ( were investigated, the existence of a relationship between each of them with the level of SOD enzyme due to its relationship with free radicals and due people exposed to smoking their body's efforts to adapt to the constant challenges they face. The results of the current study showed there is a significant differences (p<0.05) of CRP, the mean of CRP in patient was9.853 mg / dl while the mean of the CRP in the control was 4.917 mg / dl. Our results revealed significant differences (p<0.05) in WBC and P.C.V. The mean of WBC in patient was7.41 x103/μL while the mean of the WBC in the control was 6.98 x103/μL significant high due to the body's immune response to protect the body from the harmful effects
Keywords: SOD. CRP. Smoke. WBC. CBC